Political persona 2016 - an introduction - David Marshall; Neil Henderson (2016)
This essay maps and charts research that has investigated political persona. It builds the claim that our representational system that has been organised through both media and politics is breaking down and the "leviathan" that such a system has legitimated is now destabilized. As a presentational media and cultural regimes rises there is now political turbulence exhibited through online activity and the current generation of political personas. It uses this premise to explain both Brexit and the rise and success of Donald Trump in the 2016 US presidential campaign.